THE EFFECT OF TAX AVOIDANCE ON COMPANY VALUE IN INDONESIA - Sindy - (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The aim of the findings of this research is to discover and investigate how tax avoidance affects firm value in Indonesia. State ownership, foreign ownership, company size also affect the value of companies in Indonesia. This research argues that tax evasion and other elements do not necessarily add value to Indonesian firms. Data from entities listed as LQ45 on the Indonesia Stock Exchange between 2017 and 2021 which of course can be used in findings based on this research. Purposive sampling is the procedure used when collecting research samples. The population of entities listed on the IDX is 810 companies, of which 45 companies are included in the LQ45 sample with a total sample data of 225. The findings based on this study prove that tax avoidance, state ownership and foreign ownership are not necessarily capable of having a significant effect on firm value, while company size is certainly capable of providing a positive influence on firm value.